2017
DOI: 10.1074/mcp.m117.067488
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-specific Protein Interactomes of Glucocorticoid and Androgen Receptor as Revealed by Proximity Mapping

Abstract: Glucocorticoid receptor (GR) and androgen receptor (AR) are steroid-inducible transcription factors (TFs). The GR and the AR are central regulators of various metabolic, homeostatic and differentiation processes and hence important therapeutic targets, especially in inflammation and prostate cancer, respectively. Hormone binding to these steroid receptors (SRs) leads to DNA binding and activation or repression of their target genes with the aid of interacting proteins, coregulators. However, protein interactom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 83 publications
(69 reference statements)
8
64
1
Order By: Relevance
“…Therefore, it was proposed that GR can functionally replace the AR, when AR signaling is blocked. Consistently, it has been shown that both receptors not only exhibit a significant overlap in their transcriptome (18), but also share several interacting proteins (21). In line with these observations, stimulation of GR activity could rescue cells from enzalutamide-induced cell death (18).…”
Section: Introductionsupporting
confidence: 60%
“…Therefore, it was proposed that GR can functionally replace the AR, when AR signaling is blocked. Consistently, it has been shown that both receptors not only exhibit a significant overlap in their transcriptome (18), but also share several interacting proteins (21). In line with these observations, stimulation of GR activity could rescue cells from enzalutamide-induced cell death (18).…”
Section: Introductionsupporting
confidence: 60%
“…In this technique, a biotin ligase, BirA, was fused to the N-terminal part of GR, and the gene was stably integrated in the cells and expressed at physiological levels, enabling BirA biotinylation of proteins based on their proximity (30). This strategy has recently been shown to be particularly amenable for nuclear receptors such as the GR and androgen receptor (31).…”
Section: Tnf Pretreatment Did Not Affect Nuclear Translocation or Grmentioning
confidence: 99%
“…In this manner, occupancy of the LBP by ligands regulates the dynamics and stability of surfaces that recognize coregulators and is thus allosterically coupled to the recruitment of these proteins to the AR (Estébanez-Perpiñá et al 2005, Estebanez-Perpina et al 2007. Albeit a recent proteomics study has identified the essentially overlapping, agonist-specific interactomes of both AR and GR (Lempiäinen et al 2017), the detailed molecular determinants of NR binding to a large number of coregulators are far from being well understood.…”
Section: Allosteric Modulation Of Ar Activitymentioning
confidence: 99%
“…These NR coregulators underlie the tissue-selective actions of NR ligands and are also emerging therapeutic targets per se, although they have proved hard to target so far (Yi et al 2015, Wang et al 2016, Ruggero et al 2018. All NR domains have been involved in coregulator recruitment and macromolecular complex formation, although the atomic details still remain elusive (Dasgupta et al 2014, Foley & Mitsiades 2016, Giudici et al 2016, Lempiäinen et al 2017.…”
Section: Introductionmentioning
confidence: 99%